Establishment and Management of Community Sanitary Complexes in Rural Areas : A Handbook - Ministry of Rural Development; World Bank (New Delhi, 2014)
Indian remains one of the countries wherein a lot of efforts are still required to eliminate the practice of open defecation. In rural areas, open defecation though reduced in scale continues to be a socially and culturally accepted traditional behavior largely. Low awareness of the potential health and economic benefits of better sanitation and hygiene practices, perception of high costs of having a toilet, the perceived convenience of open defecation are some of the other bottlenecks towards achievement of the goal of open defecation free India. Lack of priority to safe confinement and disposal of human excreta poses significant health risks manifest in the sanitation challenge facing the nation today. However, the Total Sanitation Campaign (TSC) launched by Government of India in 1999 has gone a long way in achieving and sustaining the status of open defecation free Gram Panchayats in rural India and ensuring healthy and hygienic environment. The vigorous efforts made under this Campaign have helped to achieve rural sanitation coverage to an estimated 70 per cent as of March 2011. The campaign has proved to be one of the most effective programs for its focus on community-led, demand driven approach, making long term positive impact on the health profiles and quality of lives of millions of rural people. The campaign has developed strategic components to ensure full coverage of sanitation through financial and programmatic support in software and hardware component of household, school, anganwadi and community sanitation. The handbook may also be useful for district and state functionaries involved in the implementation of the TSC. It may also be of interest to other professionals and entrepreneurs working in the field of rural sanitation.